2021
DOI: 10.1016/j.appet.2020.104860
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of conventional and alternative protein sources: A mixed-methods approach with meal and product framing

Abstract: Understanding consumer perceptions of meat alternatives is key to facilitating a shift toward more sustainable food consumption. Importantly, these perceptions may vary according to the characteristics of the consumer (e. g., preferences, motivations), the product (e.g., sensory attributes) and the encounter (e.g., how the meat alternative is presented/framed). Qualitative and quantitative methods were applied to examine consumer perceptions of five proposed alternatives to meat: legumes, tofu, seitan, lab-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 41 publications
7
41
0
1
Order By: Relevance
“…Respondents of the online survey perceived the use of pulses as healthy, inexpensive and sustainable, which was in line with other recent consumer studies (Possidonio, Prada, Graca, & Piazza, 2021;Smiglak-Krajewska, Wojciechowska-Solis, & Viti, 2020). Possidonio et al (2021) assessed consumer mindsets towards alternatives of meat and found that legumes, such as chickpeas, beans, peas and lentils, were considered the most natural, appetizing, healthy, edible, ethical, sustainable, least processed and overall, the most positive and familiar products compared to other meat alternatives, such as seitan, insects and lab-grown meat. Smiglak-Krajewska et al Accepted manuscript (2020) concluded, in their questionnaire study, that peas, beans, soybeans and lentils were the most recognized and most frequently consumed legumes.…”
Section: Online Surveysupporting
confidence: 89%
“…Respondents of the online survey perceived the use of pulses as healthy, inexpensive and sustainable, which was in line with other recent consumer studies (Possidonio, Prada, Graca, & Piazza, 2021;Smiglak-Krajewska, Wojciechowska-Solis, & Viti, 2020). Possidonio et al (2021) assessed consumer mindsets towards alternatives of meat and found that legumes, such as chickpeas, beans, peas and lentils, were considered the most natural, appetizing, healthy, edible, ethical, sustainable, least processed and overall, the most positive and familiar products compared to other meat alternatives, such as seitan, insects and lab-grown meat. Smiglak-Krajewska et al Accepted manuscript (2020) concluded, in their questionnaire study, that peas, beans, soybeans and lentils were the most recognized and most frequently consumed legumes.…”
Section: Online Surveysupporting
confidence: 89%
“…For instance, in some regions of the world it is not possible to economically grow agricultural crops but it is still possible to rear livestock for food, for example, steep or rocky hills. Another reason driving some consumers to reduce their consumption of animal products is related to their ethical concerns about the confining and slaughtering of huge numbers of animals per year (Leiserowitz, Ballew, Rosenthal, & Semaan, 2020; Possidonio, Prada, Graca, & Piazza, 2021). Finally, many consumers are adopting a more plant‐based diet because they believe it is healthier than an animal‐based one, which is also driving changes in consumer preferences, but this depends on the types of plant‐ and animal‐based foods consumed (Hemler & Hu, 2019; Possidonio et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason driving some consumers to reduce their consumption of animal products is related to their ethical concerns about the confining and slaughtering of huge numbers of animals per year (Leiserowitz, Ballew, Rosenthal, & Semaan, 2020; Possidonio, Prada, Graca, & Piazza, 2021). Finally, many consumers are adopting a more plant‐based diet because they believe it is healthier than an animal‐based one, which is also driving changes in consumer preferences, but this depends on the types of plant‐ and animal‐based foods consumed (Hemler & Hu, 2019; Possidonio et al., 2021). For instance, fresh or minimally processed plant‐based foods such as fruits, vegetables, nuts, and whole grains have been linked to improved nutrition, but highly processed ones like many of the current generation of plant‐based meat analogs may not provide nutritional benefits because they often contain high levels of saturated fat, salt, and digestible carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…While a noteworthy amount of research has been undertaken to understand why individuals transition to a vegan or vegetarian diet, the findings from these studies do not necessarily provide accurate insight for companies to model their businesses on [29][30][31][32]. Our knowledge of the value proposition for vegan food thus remains uncertain.…”
Section: Introductionmentioning
confidence: 99%